INTEGRASI EDUKASI HUKUM DAN KESEHATAN SEBAGAI UPAYA MENGURANGI RISIKO PENYALAHGUNAAN NARKOTIKA DI WILAYAH LEUWILIANG KABUPATEN BOGOR - DITA ARINI; Uta Provinsiana Sukmara (LPPM Universitas Abdurrab, 2026)
This community service activity aims to improve the understanding of village officials and teenagers in Leuwiliang Village, Bogor Regency, about the dangers of drug abuse through an integrated approach that combines legal and health aspects. This program is motivated by the low literacy of the community regarding criminal sanctions, rehabilitation mechanisms, and the physical and psychological impacts of drugs. The implementation methods include socialization, interactive discussions, and legal case simulations combined with health education. Evaluation was conducted using pre-tests and post-tests with 25 participants. The pre-test results showed that most participants did not understand criminal sanctions (80%), rehabilitation mechanisms (84%), and the physical and psychological impacts of drugs. After the counseling, the post-test results showed a significant increase, with 100% of participants understanding legal aspects, rehabilitation policies, and the physical and psychological impacts of drugs. These findings indicate that an integrated approach based on law and health is effective in improving community literacy and preventive awareness. This program is recommended to be carried out continuously through collaboration between the village government, academics, and health workers to strengthen social resilience against the threat of drugs.